Spontaneous Splenic Rupture due to Metastatic Pancreatic Cancer. (6th September 2021) - Politis, D.; Myoteri, D.; Bourou, M.; Nastos, C.; Papaconstantinou, I.; Dellaportas, D.
Abstract : Introduction . Nontraumatic splenic rupture is a rare event. On the other hand, splenic metastasis is also rare and usually found in the context of disseminated disease. Spontaneous splenic rupture caused by a metastatic deposit has been reported only as case reports. To the best of our knowledge, pancreatic cancer being the primary site has been reported in only a handful of cases. Case Presentation . A case of spontaneous splenic rupture in a 68-year-old male presenting with acute onset left shoulder pain, caused by metastatic pancreatic cancer to the spleen, is presented herein. During the investigation, the patient developed hypovolemic shock due to intra-abdominal hemorrhage, necessitating emergency splenectomy. The patient recovered well and was discharged from the hospital on the 8 th postoperative day. Discussion . This study underlines the fact that the spleen is a rare site of metastasis, remaining mostly asymptomatic. However, it can nevertheless prove to be a life-threatening condition. The exact pathophysiological mechanism of splenic rupture due to metastasis still remains unknown, requiring further research. Emergency splenectomy remains the standard of care, and this clinical condition should be considered in the differential diagnosis of cases with acute abdomen and malignant neoplasm history.